Trauma, Autism, and Neurodevelopmental Disorders Integrating Research, Practice, and Policy (Springer International Publishing, 2018)
This book examines the diagnostic overlap and frequent confusion between the newly named DSM-5 diagnostic categories of neurodevelopmental disorders (NDDs), which include autism spectrum disorder (ASD), and trauma and stressor related disorders (TSRDs). These conditions are similar in that a) children with developmental disorders are particularly vulnerable to traumatic events and b) all have pervasive effects on the brain and development. Chapters provide a wealth of effective clinical, family, and school-based interventions, developed from established studies and important new findings. In addition, chapters use illustrative case studies to survey assessment challenges in today's healthcare climate and consider alternative routes for improving correct diagnoses, identifying appropriate interventions, and referring proper targeted, evidence-based treatment and services. The book concludes with the editors' recommendations for needs-based service access, including a more widespread use and acceptance of the Research Domain Criteria (RDoC) and the International Classification of Functioning, Disability, and Health (ICF) framework. Topics featured in this book include: The neurobiological contributors to posttraumatic stress disorder (PTSD). Fetal alcohol spectrum disorders (FASDs) and its diagnosis in children with a history of trauma. Interventions for trauma and stressor-related disorders in preschool-aged children. Reactive attachment disorder (RAD) and autism spectrum disorder (ASD) diagnosis and care in a cultural context. Special population consideration in ASD identification and treatment. Challenges associated with the transition to adulthood. Trauma and neurodevelopmental disorders from a public health perspective. Trauma, Autism, and Neurodevelopmental Disorders is a must-have resource for researchers, clinicians and related professionals, and graduate students in developmental psychology, child and adolescent psychiatry, public health, social work, pediatrics, and special education.